2007
DOI: 10.1177/0013164406294781
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Purification and Effect Size Use With Logistic Regression for Differential Item Functioning Detection

Abstract: Two unresolved implementation issues with logistic regression (LR) for differential item functioning (DIF) detection include ability purification and effect size use. Purification is suggested to control inaccuracies in DIF detection as a result of DIF items in the ability estimate. Additionally, effect size use may be beneficial in controlling Type I error rates. The effectiveness of such controls, especially used in combination, requires evaluation. Detection errors were evaluated through simulation across i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
107
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(126 citation statements)
references
References 33 publications
18
107
0
1
Order By: Relevance
“…However, a carefully designed purification procedure needs to be the first step for identifying potential DIF items when conducting DIF analyses with real data. In the literature, different anchor purification methods have been suggested to select DIF-free items for different DIF detection approaches (e.g., French and Maller, 2007;Wang et al, 2009;Woods, 2009b;Gonzalez-Betanzos and Abad, 2012). Depending on the selection of DIF-free items (i.e., purification), the DIF detection methods may provide different results regarding the number and type of detected DIF items.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…However, a carefully designed purification procedure needs to be the first step for identifying potential DIF items when conducting DIF analyses with real data. In the literature, different anchor purification methods have been suggested to select DIF-free items for different DIF detection approaches (e.g., French and Maller, 2007;Wang et al, 2009;Woods, 2009b;Gonzalez-Betanzos and Abad, 2012). Depending on the selection of DIF-free items (i.e., purification), the DIF detection methods may provide different results regarding the number and type of detected DIF items.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Scale levels were estimated by the sum score, including also the item being tested [26,30,31]. Other items with DIF were excluded from the sum score, i.e., it was purified [26,32].…”
Section: Methodsmentioning
confidence: 99%
“…to unrefined results both in terms of Type I and Type II error. Recent reviews of the refinement literature (Colvin & Randall, 2011;French & Maller, 2007) concluded that refinement was typically found to have a favorable effect on the accuracy of DIF procedures.…”
Section: Criterion Refinement In Differential Item Functioning Analysesmentioning
confidence: 99%